Black, Grey and Watch Lists of alien species in the Czech Republic based on environmental impacts and management strategy - Pergl, Jan; Sádlo, Jiří; Petrusek, Adam; Laštůvka, Zdeněk; Musil, Jiří; Perglová, Irena; Šanda, Radek; Šefrová, Hana; Šíma, Jan; Vohralík, Vladimír; Pyšek, Petr (. NeoBiota. - [s.l.] : Pensoft, 2011-. - Online-Ressource. - ISSN 1314-2488, 2016)
As legislation, research and management of invasive alien species (IAS) are not fully coordinated across countries or different stakeholder groups, one approach leading to more or less standardized activities is based on producing lists of prominent IAS that attain high level of concern and are a subject of priority monitoring and management. These so-called Black, Grey and Watch (alert) Lists represent a convenient starting point for setting priorities in prevention, early warning and management systems. It is important that these lists be based on transparent and robust criteria so as to accommodate interests and perception of impacts by groups of concerned authorities and stakeholders representing sectors as diverse as, e.g. forestry, horticulture, aquaculture, hunting, and nature conservation, and to justify possible trade restrictions. The principles for blacklisting need to be general enough to accommodate differences among taxonomic groups (plants, invertebrates, vertebrates) and invaded environments (e.g. aquatic, terrestrial, urban, suburban, seminatural), and must take into account invasion dynamics, the impact the IAS pose, and management strategies suitable for each particular invader. With these assumptions in mind, we synthesize available information to present Black, Grey and Watch Lists of alien species for the Czech Republic, with recommended categorized management measures for land managers, policy makers and other stakeholders. We took into account differences in the listed species’ distribution, invasion status, known or estimated environmental impact, as well as possible management options, and apply these criteria to both plants and animals. Species with lower impact, but for which some level of management and regulation is desirable, are included on the Grey List. Some potentially dangerous species occurring in European countries with comparable climatic conditions, as well as those introduced in the past but without presently known wild populations in the Czech Republic, are listed on the Watch list. In total, there are 78 plant and 39 animal species on the Black List, 47 and 16 on the Grey List, and 25 and 27, respectively, on the Watch List. The multilayered approach to the classification of alien species, combining their impacts, population status and relevant management, can serve as a model for other countries that are in process of developing their Black Lists.